Ethnic Stereotypes in the Film Kaka Boss: Representation of Eastern Indonesians - Putra Dwi Pangestu; Arif Ardy Wibowo (Institut Agama Islam Negeri (IAIN) Curup, 2026)
ABSTRACT Purpoese − This study aims to examine how stereotypes toward people from Eastern Indonesia are represented in the film Kaka Boss and the role of the film in reinforcing or challenging stereotypes that circulate in society. Method − This research employs a qualitative approach using Roland Barthes’ semiotic analysis, focusing on three levels of meaning: denotation, connotation, and myth, as applied to selected scenes in the film, with the concepts of stereotype and representation theory serving as the interpretive framework. Findings − The findings indicate that stereotypes related to violence, harsh behavior, and criminal tendencies are not portrayed as inherent traits of the main character, but rather as social constructions imposed by the surrounding environment. Through the responses of the character Kaka Boss in various conflict situations, the film presents a reversal of meaning toward social myths that associate assertiveness and the physical appearance of people from Eastern Indonesia with violence. Thus, Kaka Boss tends to offer a deconstruction of stereotypes by presenting representations of people from Eastern Indonesia that are more humanistic, complex, and dialogical.